ANALISIS KARAKTERISTIK SIFAT KIMIA TANAH GAMBUT SETELAH DIINKUBASI DENGAN KASCING DARI CAMPURAN KOTORAN AYAM, BONGGOL PISANG DAN AMPAS TAHU - Riopy Suanda; Hilwa Walida; Khairul Rizal; Kamsia Dorliana Sitanggang (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2022)
Peat soil has a high cation exchange capacity, low base saturation, has a low content of K, Ca, Mg, P and also has a low content of micro elements (such as Cu, Zn, Mn and B). This study aims to determine the chemical properties of peat soil that has been incubated with vermicompost fertilizer from a mixture of banana weevil, chicken manure and tofu dregs. The test was carried out by mixing peat soil and vermicompost according to the treatment in 2 kg polybags. After thoroughly stirring, the mixture was sprinkled with peat water once a day until it reached field capacity. The mixture was then incubated for 2 weeks. Each treatment was repeated 3 times. This study was conducted with a non-factorial randomized design as follows: PO = Control (1 kg of peat soil), P1 = 1 kg of peat + 500 grams of vermicompost, P2 = 1 kg of peat soil + 1 kg of vermicompost and Based on the results of the research analysis can be taken the conclusion that peat soil incubated for two weeks increased the chemical properties of the soil, namely: improving pH by P1 0.15 units and P2 by 0.175 units, total N by 0.43% and P2 by 0.755 %, P by P1 733.52 and P2 was 922,015, K was 2,145 and P2 was 2,575, Ca was 1,675 and P2 was 2,825, Mg was P1 3 and P2 was 4,27 and increased Na by 0,09 and P2 by 0,045.